Laras concept and its triggers: A case study on garap of jineman Uler Kambang - Widodo, Widodo; Ganap, Victor; Soetarno, Soetarno (Harmonia: Journal of Arts Research and Education, 2017)
Laras is one unresolved aesthetic concept and gendhing garap models as the triggers have not been identified yet either. This paper is a case study which discusses a case of jineman garap Uler Kambang pélog lima, the first winner of Sindhèn Idol contest 2012, which is considered to have the most qualified performance to meet laras criteria. The purpose of this research is to figure out the laras concept construction and identify the gendhing garap models as its triggers. Laras concept reconstruction within the aesthetic framework of Javanese karawitan and identification of gendhing garap model are discussed based on concept of garap in Javanese karawitan. This research uses a qualitative-descriptive method. The results show that laras is a beautiful, delicate, and deep karawitan sense containing elements of mat, lega, betah, adhem, ayem, tentrem, jinem, sengsem, and marem. The triggering gendhing garap models include: garap of leres, rempeg, greget-urip, and sarèh-sumèlèh.